Ruang Tamping Sebagai Simbol Kebangsawanan Rumah Tradisional Bugis di Bone Sulawesi Selatan - Akbar Andi Muhammad; Azis Alimuddin (Universitas Muslim Indonesia, 2021)
The design of the space in the traditional Bugis noble house in Bone is generally divided into three horizontal spaces, namely: lontang ri'saliweng, lontang ri'tenggah and lontang ri'laleng which are connected by a tamping room as a circulation path. With a distinctive shape as a symbol of Bugis Bone nobility, the tamping room needs to be investigated more deeply as a work of local architecture to connect the works of national architecture in the past and the future. The purpose of this study is to reveal the characteristics of the tamping room as a symbol of the traditional architecture of the Bugis noble house in Bone. This research was conducted based on the Bugis kingdom in the former Bone Regency. This researchmethodology is qualitative with a naturalistic paradigm approach. The results of this study, symbolically the tamping room can influence people's perceptions as a differentiating space for social strata in the house with its spatial form extending backward linearly with the existing spaces in Indo bola and located parallel to the main door as a symbol of limitation of human movement space marked by a clear separation of space. and firm in the form of differences in the height and low of the floor. The higher the difference in floor height as a symbol, the higher the degree of nobility, and the wider the size of the tamping room, the more rules that limit it.